Migración rural urbana e informalidad en las zonas metropolitanas de México. Una estimación de corto plazo - Lara, Jaime; Cruz Yedra, Marla; Moyeda López, Diana V.; Prats Molina, Adriana; Téllez Muñoz, José A. (El Colegio de México, A.C., 2020)
We estimate the impact of rural-urban migration from the period 2010-2015 on informality in metropolitan areas of Mexico. The estimation of ordinary least squares does not establish any eﬀect, while the estimation with instrumental variables ﬁnds that exogenous rural urban migration increases informality. Other variables such as unemployment, labour participation and inequality are unaﬀected, indicating that informal sector allows to absorb changes in labour supply in the short term, albeit with possible negative eﬀects on labour income of substitute workers.